(untitled) (Journal of Partial Differential Equations, 2023)
Using a novel approach, we present explicit criteria for the quasi contraction of stochastic functional differential equations. As an application, some sufficient conditions ensuring the contraction property of the solution to the considered equations are obtained. Finally, some examples are investigated to illustrate the theory.